Hearing atoms hopping in a crystalline ionic conductor - Yoyo Hinuma (Science and Technology of Advanced Materials: Methods)
Molecular dynamics (MD) simulations study the trajectories of hundreds of atoms over tens of thousands of steps. Atom hops in crystalline ionic conductors are distinguishable events between discrete and well-defined sites in the crystal. A procedure to sonify information on such atom hops was developed. Changes in atom coordinate values are converted to a non-negative hopping signal, and sudden changes caused by hopping are detected as peaks in the signal. Atom hops can be ‘heard’ by using the hopping signal as an envelope of an arbitrary audio signal. Identifying where, when and how often atoms hop is much easier using audio information compared to using a video image of moving atoms. Superimposing sounds with different frequencies provide information on the hopping of different groups of atoms, and translating imperceptible scientific phenomena into a piece of appealing artistic audio performance may be appraised by the general public.